(untitled) (Ustozlar uchun, 2025)
The integration of technology in education has transformed traditional teaching and learning methodologies, enhancing accessibility, engagement, and personalization. This paper explores the various ways technology facilitates educational processes, including the use of digital tools, online resources, and interactive platforms. It examines the impact of technology on student engagement, collaborative learning, and the development of critical thinking skills. Furthermore, the paper discusses challenges such as the digital divide and the need for teacher training in technology integration. Overall, the findings underscore the potential of technology to enrich education and prepare students for a rapidly evolving digital world.